2021
DOI: 10.3390/s21165675
|View full text |Cite
|
Sign up to set email alerts
|

Processing Chain for Localization of Magnetoelectric Sensors in Real Time

Abstract: The knowledge of the exact position and orientation of a sensor with respect to a source (distribution) is essential for the correct solution of inverse problems. Especially when measuring with magnetic field sensors, the positions and orientations of the sensors are not always fixed during measurements. In this study, we present a processing chain for the localization of magnetic field sensors in real time. This includes preprocessing steps, such as equalizing and matched filtering, an iterative localization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The resonance peak shift can be attributed to the influence of magnetic field on the Young's modulus, i.e. the delta-E effect [38][39][40]. Comparing Figure 2a and 2b, it is interesting to note that the at =2.5 Oe is dramatically enhanced by twice than that at zero field.…”
Section: Resultsmentioning
confidence: 88%
“…The resonance peak shift can be attributed to the influence of magnetic field on the Young's modulus, i.e. the delta-E effect [38][39][40]. Comparing Figure 2a and 2b, it is interesting to note that the at =2.5 Oe is dramatically enhanced by twice than that at zero field.…”
Section: Resultsmentioning
confidence: 88%
“…However, when the AC field frequency was scanned under a DC bias field of 2.5 Oe, the peak frequency shifted from 60.041 kHz to 60.101 kHz ( Figure 2 b). The resonance peak shift can be attributed to the influence of the magnetic field on Young’s modulus, i.e., the delta-E effect [ 39 , 40 , 41 ]. When comparing Figure 2 a,b, it is interesting to note that at = 2.5 Oe was dramatically enhanced to twice that under the zero field.…”
Section: Resultsmentioning
confidence: 99%
“…By exemplary, applying the introduced evaluation methods, it can be concluded that especially the electrically modulated ME sensor system has the potential to measure a magnetic heart signal, at least by applying advanced averaging techniques [ 52 ]. The other presented ME sensor type is better suited for applications where only a small frequency range is necessary, such as active magnetoelectric motion sensing [ 13 ] or ME sensor localization [ 12 ]. Nevertheless, cardiovascular medicine requires an unaveraged MCG morphology (QRS complex, P-wave, and T-wave) in the time domain, especially as cardiac arrhythmias manifest from beat to beat [ 7 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exchange bias magnetoelectric sensor is used to demonstrate a typical resonant ME sensor system. This sensor type is especially applicable for detecting narrowband signals, for example, coil signals utilized in novel ME localization [ 12 ] and ME movement detection applications [ 13 ]. In contrast to this, the electrically modulated ME sensor is potentially better suited for broadband biomedical signals due to a much higher bandwidth.…”
Section: Exemplary Evaluation Of Magnetoelectric Sensor Systemsmentioning
confidence: 99%
See 1 more Smart Citation